Wyprawa cesarza Septymiusza Sewera do Brytanii w latach 208-211 w świetle źródeł historiograficnzych i numizmatycznych = The 208-211 expedition of emperor Septimius Severus to Britain in historiographical and numismatic sources - Janiszewska-Sieńko, Daria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The expedition emperor Septimius Severus made to Britain in years 208-211 was the last military campaign in the life of this first representative of the Severus dynasty. Its impact can be found in numerous historiographical, numismatic and insctiptive sources.
Keywords: Septymiusz Sewer (cesarz rzymski; 146-211); Wielka Brytania; źródła historiograficzne; źródła numizmatyczne; 3 w.